2004
DOI: 10.1108/09615530410539937
|View full text |Cite
|
Sign up to set email alerts
|

The two‐fluid modelling of gas‐particle transport phenomenon in confined systems considering inter particle collision effects

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Woo et al [1988] argued that when C max > 0.04, the models developed for dilute flows do not work. Greimann and Holly [2001] and Mitter et al [2004] adopted the value C max = 0.1 for the threshold beyond which the flow is nondilute. This raises the basic and very important question about the range of validity of the models developed for dilute and nondilute cases.…”
Section: Introductionmentioning
confidence: 99%
“…Woo et al [1988] argued that when C max > 0.04, the models developed for dilute flows do not work. Greimann and Holly [2001] and Mitter et al [2004] adopted the value C max = 0.1 for the threshold beyond which the flow is nondilute. This raises the basic and very important question about the range of validity of the models developed for dilute and nondilute cases.…”
Section: Introductionmentioning
confidence: 99%
“…The only difference is the inclusion of particle collision in the results shown to the right of Figure 2(b). Previous studies by Mitter et al (2004) and Gorman and Sparrow (2018) have reported the importance of inter-particle collision on the coarse particle transport properties in gas-solid turbulent flows. The results from the present study also support the previous conclusion about the influence of inter-particle collision in particle transport.…”
Section: Resultsmentioning
confidence: 99%
“…The key to understanding erosion is a detailed knowledge of coupled and complex fluid/solids interactions (Mitter et al, 2004;Habib et al, 2005). Because of experimental difficulties, solids motion studies are not common.…”
Section: Introductionmentioning
confidence: 99%